Chemotherapy, Delayed Radiation and Brain Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
To avoid the severe irradiation-related neurotoxic effects of postoperative treatment of malignant brain tumors in infants and children less than 3 years of age, the Pediatric Oncology Group, centered at St Louis, MO, conducted a prospective study of primary postoperative chemotherapy.